MEMPERTIMBANGKAN KEMBALI RAJA PEMBARU JAWA: ANALISIS FUNGSIONAL PADA GAYA PEMERINTAHAN RAJA AIRLANGGA PADA ABAD KE-11 M - Muhamad Alnoza (Handep: Jurnal Sejarah dan Budaya, 2022)
This paper critically discusses Airlangga’s style of government using the functional analysis approach proposed by Robert K. Merton. The problem raised in this study is how Airlangga performs his function as a king in his royal government. The study aims to find out the functions of manifest, latent functions, and dysfunctional aspects of Airlangga through the policies he issued. The method used in this qualitative research consisted of data collection through library research and data processing by analyzing and interpreting. By comparing Airlangga policy and the concept of , the study has found that Airlangga carried out manifest function in military and economy. In the meantime, he carried out the latent function in the international relations. Airlangga’s dysfunctional aspect has shown Airlangga’s lack of functioning as the symbol of the glory of a country and the guardian of the kingdom’s internal stability. Therefore, the novelty of the research is Airlangga’s position as a dysfunctional figure in one of the aspects that a king was supposed to own